Trauma-Related Knowledge and Practice Changes among Brokers in a Community-Based Learning Collaborative. (September 2022) - Are, Funlola; Saunders, Benjamin; Peer, Samuel; Ralston, Elizabeth; Hanson, Rochelle F.
Purpose: Broker professionals serve an important intermediary role in improving service access for youth but are often trained separately from clinicians. Community-Based Learning Collaboratives (CBLCs) include specific training/implementation strategies to foster collaboration and build community capacity for EBPs.Methods: The current study examined changes in trauma-related knowledge, practices, organizational culture, and interprofessional collaboration among 63 brokers. Brokers reported significant positive changes in trauma-related knowledge, practices, organizational culture, and interprofessional collaboration following CBLC participation.Results: Hierarchical regression analyses indicated statistically significant improvements in knowledge of treatment planning/case monitoring ( r = .41) and organizational culture ( r = .30) as significant predictors of changes in brokers' use of child trauma evidence-based practices following CBLC participation.Discussion: Findings emphasize tailoring training to include topics and strategies most relevant to participants' day-to-day responsibilities.